Philosophy as involuntary self-confession: The Nietzsche of Lou Andreas-Salomé - Nogueira do Rêgo Monteiro Villa, Lucas (Pensando - Revista de Filosofia, 2026)
This article explores Lou Andreas-Salomé’s (1992) interpretation of Friedrich Nietzsche’s work in her “Friedrich Nietzsche in His Works,” focusing on her psychological and existential reading of Nietzsche’s central concepts. Salomé proposes a profound connection between life and work, arguing that Nietzsche developed his philosophy as a personal response to the crisis of Western values. The article examines Salomé’s three main interpretative axes: a) the relationship between Nietzsche’s personal experiences and his philosophy, seen as a kind of “involuntary self-confession”; b) Nietzsche’s multifaceted writing style, revealing a fragmented spirit resulting from the conflict and attempted reconciliation of various distinct identities (the musician, the poet, the philosopher, the philologist, the religious), in perpetual metamorphosis and self-overcoming; c) the mystical dimension of Nietzsche’s final “system,” exposing a divine ideal of transcendence projected in concepts like Eternal Recurrence, Overman, and Will to Power. Ultimately, these analyses are situated within the broader Nietzschean interpretive community, drawing panoramic comparisons with commentators like Walter Kaufmann, Martin Heidegger, Karl Jaspers, Gilles Deleuze, Michel Foucault, Gianni Vattimo, and Alexander Nehamas, revealing the originality and influence of Salomé’s perspective in Nietzschean studies.